2016
DOI: 10.1080/00140139.2016.1164902
|View full text |Cite
|
Sign up to set email alerts
|

Response of the seated human body to whole-body vertical vibration: discomfort caused by mechanical shocks

Abstract: The frequency-dependence of discomfort caused by vertical mechanical shocks has been investigated with 20 seated males exposed to upward and downward shocks at 13 fundamental frequencies (1 to 16 Hz) and 18 magnitudes (±0.12 to ±8.3 ms -2 ). The rate of growth of discomfort with increasing shock magnitude depended on the fundamental frequency of the shocks, so the frequencydependence of equivalent comfort contours (for both vertical acceleration and vertical force measured at the seat) varied with shock mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…Whereas sinusoidal vibration is dominated by a single frequency, a mechanical shock always has a frequency content that includes a wide range of frequencies. The discomfort caused by vertical sinusoidal vibration has been reported by Zhou and Griffin (2014b) and the discomfort caused by vertical mechanical shocks has been reported by Zhou and Griffin (2017b). Over the frequency range 1 to 16 Hz their studies confirmed that with increasing magnitude of both types of motion the rate of growth of discomfort decreased as the fundamental frequency of the motion increased, consistent with some previous studies (e.g.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Whereas sinusoidal vibration is dominated by a single frequency, a mechanical shock always has a frequency content that includes a wide range of frequencies. The discomfort caused by vertical sinusoidal vibration has been reported by Zhou and Griffin (2014b) and the discomfort caused by vertical mechanical shocks has been reported by Zhou and Griffin (2017b). Over the frequency range 1 to 16 Hz their studies confirmed that with increasing magnitude of both types of motion the rate of growth of discomfort decreased as the fundamental frequency of the motion increased, consistent with some previous studies (e.g.…”
Section: Introductionsupporting
confidence: 84%
“…The shocks were presented so that the motion moved up from the starting position and then returned to the starting position ( Figure 1). A previous study with shocks having the same waveform and similar magnitudes found no significant difference in the discomfort caused by 'upward' and 'downward' shocks (Zhou and Griffin, 2017b). Irrespective of the fundamental frequency, or whether the motion was vibration or shock, motions with similar frequency-weighted VDVs would be expected to produce broadly similar discomfort.…”
Section: Stimulimentioning
confidence: 79%
See 1 more Smart Citation
“…The rate of growth of discomfort with increasing shock magnitude depended on the fundamental frequency of the shocks, so the frequency dependence of equivalent comfort contours varied with shock magnitude. The rate of growth of discomfort was similar for acceleration and force, upward and downward shocks, and lower and higher magnitude shocks [19].…”
Section: Introductionmentioning
confidence: 76%
“…The nonlinearity in the biodynamic response to vertical mechanical shocks found here can be expected to contribute to the nonlinearity observed in subjective responses to this type of mechanical shock (Zhou and Griffin, 2016). The time-domain modelling of the biodynamic responses employed here also offers a route to modelling and optimising the dynamic responses of seats to control the discomfort and injury potential associated with mechanical shocks.…”
Section: Nonlinearity In the Vertical Nominal Apparent Massmentioning
confidence: 88%